Indeterminate solitary vertebral lesions on planar scintigraphy - Qian, Xie; Wenqi, Zhang; Shi, Gao; Bin, Chen; Qingjie, Ma; Tianji, Liu; Bin, Ji (Nuklearmedizin - NuclearMedicine, 2018)
Objective: This study aims to evaluate the added value of hybrid SPECT-CT in differential diagnosis of indeterminate solitary vertebral lesion (SVL) on planar scintigraphy in patients with non-small cell lung cancer (NSCLC).Methods: Sixty-three NSCLC patients with indeterminate “hot spot” SVL on planar scintigraphy were retrospectively included in this study. Pathological confirmation and followup by whole body scintigraphy and SPECT-CT were used as golden standard for the evaluation of diagnostic performance of planar scintigraphy, SPECT, and SPECT-CT. Receiver operating characteristic (ROC) analyses were performed and compared among the three imaging modalities. For subgroup analysis, the performance of each imaging modality in different NSCLC subgroups including age, gender, histology of primary tumor and nature, site and location of SVL were analyzed, respectively. The impact of SPECT-CT on the management of NSCLC patient with SVL was also analyzed.Results: The sensitivity and specificity of planar scintigraphy, SPECT, and SPECT-CT in differentiating SVL were 41.9 % and 81.2 %, 83.9 % and 71.9 %, and 90.3 % and 90.6 %, respectively. SPECT-CT performed significantly better than both planar scintigraphy (P < 0.0001) and SPECT (P = 0.0027). The sensitivity for planar scintigraphy in nonlytic SVL was significantly higher than in lytic SVL (88.5 % vs. 50.0 %, P = 0.0008). The sensitivity for the planar scintigraphy and SPECT-CT in dorsal SVL was significantly higher than in non-dorsal SVL (55.0 % vs. 18.2 %, P = 0.0029 and 100 % vs. 85.7 %, P = 0.0236, respectively). SPECT-CT had an impact on the clinical management of 52.6 % (20/38) of patients compared to planar scintigraphy and 23.6 % (9/38) of patients compared to SPECT.Conclusion: Compared to planar scintigraphy and SPECT, hybrid SPECT-CT shows excellent performance in differentiating indeterminate SVL in NSCLC patients, the application of which will significantly impact patient management.Ziel: Ziel dieser Studie ist es, den Mehrwert der hybriden SPECT-CT in der Differenzialdiagnose der unbestimmten solitären Knochenläsionen der Wirbelsäule (SVL) auf der planaren Szintigraphie bei Patienten mit nichtkleinzelligem Lungenkarzinom (NSCLC) zu untersuchen.Methode: Retrospektiv wurden 63 NSCLC-Patienten mit unbestimmten solitären „hot spot” Knochenläsionen der Wirbelsäule unter planarer Szintigraphie eingeschlossen. Pathologische Bestätigung und Follow-up durch Ganzkörper-Szintigraphie und SPECTCT wurden als Goldstandard für die Bewertung der diagnostischen Leistung der Planar- Szintigraphie, SPECT und SPECT-CT verwendet. ROC-Analysen (Receiver Operating Characteristic, Beobachterkennlinie) wurden erstellt und zwischen den drei Bildgebungsmodalitäten verglichen. Für die Subgruppenanalyse wurde die Leistung jeder Bildgebungsmodalität in verschiedenen NSCLC-Untergruppen einschließlich Alter, Geschlecht, Histologie des Primärtumors und der Art, Lage und Ort der SVL analysiert. Der Einfluss von SPECT-CT auf das Management von NSCLC-Patienten mit SVL wurde ebenfalls analysiert.Ergebnisse: Die Sensitivität und Spezifität der planaren Szintigraphie, SPECT und SPECT-CT bei der Differenzierung von SVL waren 41,9 % und 81,2 %, 83,9 % und 71,9 % bzw. 90,3 % und 90,6 %. Die SPECT-CT zeigte eine signifikant bessere Leistung als die planare Szintigraphie (P < 0,0001) und die SPECT (P = 0,0027). Die Sensitivität für die planare Szintigraphie bei nicht-lytischer SVL war signifikant höher als bei der lytischen SVL (88,5 % vs. 50,0 %, p = 0,0008). Die Sensitivität für die planare Szintigraphie und SPECT-CT in der dorsalen SVL war signifikant höher als in nicht-dorsalen SVL (55,0 % gegenüber 18,2 %, P = 0,0029 und 100 % gegenüber 85,7 %, P = 0,0236). SPECT-CT beeinflusste das klinische Management von 52,6 % (20/38) der Patienten im Vergleich zur planaren Szintigraphie und 23,6 % (9/38) der Patienten im Vergleich zur SPECT.Schlussfolgerung: Im Vergleich zur Planar-Szintigraphie und SPECT zeigt die hybride SPECT-CT eine hervorragende Leistung bei der Differenzierung unbestimmter SVL bei NSCLC-Patienten, deren Anwendung das Patientenmanagement signifikant beeinflussen wird.
Keywords: Non-small cell lung cancer; solitary vertebral lesion; planar scintigraphy; SPECT-CT; patient management